Prognostic significance of the co-expression of EGFR and HER2 in adenocarcinoma of the uterine cervix. - Asako Ueda; Akira Takasawa; Taishi Akimoto; Kumi Takasawa; Tomoyuki Aoyama; Yoshihiko Ino; Masanori Nojima; Yusuke Ono; Masaki Murata; Makoto Osanai; Tadashi Hasegawa; Tsuyoshi Saito; et al. (PLoS ONE, 2017)
Prognostic factors and therapeutic targets are needed for the patients with cervical adenocarcinoma because they have a poor prognosis. Recently, co-expression of multiple receptor tyrosine kinases (RTKs) has been found to be associated with aggressive biological behavior and poor prognosis of several types of malignancy. To evaluate the significance of the expression of multiple RTKs in uterine cervical cancers, we examined the expression profile of RTKs (EGFR, HER2 and c-Met) and the correlation of their expression with clinicopathological features and prognosis of patients with cervical adenocarcinomas. AIS and adenocarcinoma showed strong expression of a single RTK (EGFR, HER2 or c-Met) on the cell membrane in 41 (77.4%) of 53 cases. Twenty (46%) of the 43 adenocarcinoma cases were positive for double or triple RTKs (P = 0.034). Positivity for EGFR and double positivity for EGFR and HER2 (EGFR+/HER2+/c-Met+ and EGFR+/HER2+/c-Met-) were significantly correlated with lymph node metastasis (P = 0.010 for single and P = 0.013 for double) and UICC stage (P = 0.021 for single and P = 0.007 for double). Positivity for HER2 was significantly correlated with tumor size (P = 0.029). Relapse-free survival (RFS) was significantly shorter in patients who were double positive for EGFR and HER2. Our results suggest that EGFR and HER2 are potential therapeutic targets and that their co-expression is a prognostic factor for cervical adenocarcinoma.